Contested issues in Christian origins and the New Testament : collected essays - Johnson, Luke Timothy (Supplements to Novum Testamentum, 2013)
In Contested Issues in Christian Origins and the New Testament, Luke Timothy Johnson offers a series of independent studies on a range of critical questions from the historical Jesus to sexuality and law.